Post-Truth Simulacra: Inviting Mutable Meaning-Making - Sameshima, Pauline (Journal of the Canadian Association for Curriculum Studies, 2017)
“Post-Truth Simulacra” is an artwork created to confront post-truth realities and constructions of meaning in response to the articles in this journal issue. An aerial photograph of Miami is used to depict the way humanity has fully operationalized the territory of the barrier islands. Various overlays are used to think about social theorist Jean Baudrillard’s precession of simulacra. Using the lens of Baudrillard's phases of representation from a pedagogical perspective, an analysis of meaning-making processes for each of the articles is discussed. The editorial recognizes the importance of place and autoethnography in the context of Canadian curriculum studies.